Characterization of two GH10 enzymes with ability to hydrolyze pretreated Sorghum bicolor bagasse - Bruno Baron, Camila Ayelen; Mon, Maria Laura; Marrero Diaz De Vill, Rubén; Cattaneo, Andrea; Di Donato, Paola; Poli, Annarita; Negri, Maria Emilia; Alegre, Mariana; Soria, Marcelo Abel; Rojo, Cecilia; Combina, Mariana; Finore, Ilaria; et al. (Springer, 2025)
In this study, we characterized two novel enzymes of the glycoside hydrolase family 10 (GH10), Xyl10 C and Xyl10E, identified in the termite gut microbiome. The activities of both enzymes were assayed using beechwood xylan, barley β-glucan, and pretreated Sorghum bicolor bagasse (SBB) as substrates. Both enzymes, assessed individually and in combination, showed activity on beechwood xylan and pretreated SBB, whereas Xyl10E also showed activity on barley β-glucan. The composition of pretreated SBB mainly consisted of xylose and arabinose content. Purified Xyl10 C showed optimum xylanase activity in the pH range 7.0–8.0 and at a temperature of 50–60 °C, while Xyl10E was active at a wider pH range (5.0–10.0) and at 50 °C. The residual activities of Xyl10 C and Xyl10E after 8 h of incubation at 40 °C were 85% and 70%, respectively. The enzymatic activity of Xyl10 C increased to 115% in the presence of 5 M NaCl, was only inhibited in the presence of 0.5% sodium dodecyl sulfate (SDS), and decreased with β-mercaptoethanol. The xylanase and glucanase activities of Xyl10E were inhibited only in the presence of MnSO4, NaCl, and SDS. The main hydrolysis enzymatic product of Xyl10 C and Xyl10E on pretreated SBB was xylobiose. In addition, the xylo-oligosaccharides produced by xylanase Xyl10E on pretreated SBB demonstrated promising antioxidant activity. Thus, the hydrolysis products using Xyl10E on pretreated SBB indicate potential for antioxidant activity and other valuable industrial applications.